Environmental Impact Assessment of 17 Construction Projects in Various University Campuses - Mora-Barrantes, Jose C. (2018)
Environmental impact assessment (EIA) is the process of evaluating the environmental consequences of a plan, policy, programme or any other project prior to the execution of the proposed action; it is the primary instrument for development planning and decision-making. Pollution sources from the construction process include harmful gases, noise, and dust, solid and liquid waste. A large variety of tools is available for environmental assessment of buildings. In Costa Rica, the EIA system is funded on the Costa Rican Political Constitution, the Environmental Organic Law and the General Regulation for the EIA Procedures of 2004. Costa Rica employs an environmental toolkit (environmental assessment form to assign the environmental impact of a new construction project. The toolkit provides a methodology, associated with environmental aspects (EAs), assessment indicators and weighting factors (WF) for each EA. A total of seven impact categories related to natural resources, soil, wildlife, flora and fauna, air, human health, water and socio-cultural are used to establish the WF. The main aim of this research was to evaluate the environmental impact of 17 construction projects to be developed in various university campuses, by using the Costa Rican toolkit. Significant environmental aspects (SEA) were determined in order to evaluate their relationship with the final value of the total environmental impact (TEIp) of each project. The results show that the TEIp for the 17 projects evaluated fall in the Low Environmental Impact category. The projects with the higher values of TEIp are those containing internal areas to handle and work with chemical and biological substances, as well as radioactive materials. From the total of the 33 EA evaluated, a 22 of them were classified as SEA. The most common SEA for the projects evaluated are treatment and disposal of ordinary wastes, treatment and disposal of debris building, emissions from mobile sources, production of noise and vibration, population density and employment generation.